(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Capacity is the ability of the organization to create value, and this ability depends on wide variety of resources, but the lack of balance between available resources and production capacity requirements leads to appearance of idle or excess capacity or appearance of deficit in capacity. Hereby, the research deals with different concepts and alternative managing models for capacity production from operational, tactical and strategic perspectives to achieve the objective of research in resolving the problems faced by imbalance capacities on production line by providing the necessary information to reach the possibility of restructuring production capacity to achieve that balance. In that light, the research is based on hypotheses that basis " there is a relationship between proposed restructuring production capacity framework and decisions of increase or reduce investment or transfers production capacity, and between restructuring production capacity to get the return on operations improvement, then increase profits". . The research found that the link between the content of proposed framework helps in getting information system which may assist the organization to managing, restructuring production capacity in the presence of constraints, and make strategic decision by increase or decrease investments, or transfer capacity from one place to another to get the return on operations improvement, then increase profits.